Studi Literatur: Gambaran Penyakit dan Pola Swamedikasi Pada Remaja di Indonesia - Wahyudi Wahyudi; Muhammad Habib Rezki Ray; Nediva Dinny Artanti; Sadza Raisya Haniya Nasution; Tyas Sasqi Regina J; Zacky Yafi Ramadhan Rambe (Lembaga Pengembangan Kinerja Dosen, 2025)
Illness is related to psychosocial disorders felt by a person, while disease is related to disorders that occur in body organs based on the diagnosis of a health profession. Options for seeking healing from a disease include going to a doctor or treating yourself or called self-medication. This study aims to determine the description of diseases and self-medication patterns that are commonly carried out by adolescents in Indonesia. The method used is a literature study of research articles published in the last 10 years and meet the inclusion criteria. The results of the literature analysis show that common diseases suffered by adolescents include flu, cough, diarrhea, anemia, skin diseases such as dandruff and tinea versicolor, digestive disorders such as ulcers, and also pain during menstruation. Around 32% of disease problems that occur in adolescents in Indonesia are nutritional problems, especially iron deficiency anemia, especially in adolescents aged 15-24 years. More extensive knowledge is needed for adolescents in Indonesia regarding the treatment of mild to moderate diseases by carrying out independent treatment/self-medication.